1973
DOI: 10.1159/000122201
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Steroid Treatment on Plasma LH and FSH in Castrated Rats from Birth to Puberty

Abstract: Rats were gonadectomized from birth to either 40 days (females) or 55 days (males) at 5-day intervals and treated for 4 days before sacrifice. Females were treated with estradiol benzoate (Eb) 0.05 µg/100 g b.w.), males with testosterone propionate (Tp) (40 µg/ 100 g b.w.), and controls with oil. At sacrifice RIA determinations were made of LH and FSH and the weights of uterus, ventral prostate and seminal vesicles recorded. In treated females plasma FSH and LH levels were lowered by treatment mainly from 20 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…A nearly physiological dose of Eb injected for 4 days in short-term ovariectomized infantile rats failed to decrease plasma FSH titers [Ojeda and R amirez, 1973] although FSH did increase after ovariectomy [Ramirez, 1972a], This finding was interpreted as indicating a relative insensitivity of the estrogen negative feedback at that age. Such a feedback can indeed be demonstrated in the infantile rat [MEUS-RoELOFse/a/., 1973;CALiGARise/a/., 1972], as revealed by the increased gonadotropin levels that followed ovari ectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A nearly physiological dose of Eb injected for 4 days in short-term ovariectomized infantile rats failed to decrease plasma FSH titers [Ojeda and R amirez, 1973] although FSH did increase after ovariectomy [Ramirez, 1972a], This finding was interpreted as indicating a relative insensitivity of the estrogen negative feedback at that age. Such a feedback can indeed be demonstrated in the infantile rat [MEUS-RoELOFse/a/., 1973;CALiGARise/a/., 1972], as revealed by the increased gonadotropin levels that followed ovari ectomy.…”
Section: Discussionmentioning
confidence: 99%
“…During neonatal and infantile days the negative feed back effects of E2 are hampered [9, 51,59] by the presence of elevated levels of alpha-fetoprotein which binds estrogens tightly [69]. At this time the predominant negative feedback signal is provided by androgens [14].…”
Section: Steroid Negative Feedbackmentioning
confidence: 99%
“…At this time the predominant negative feedback signal is provided by androgens [14]. As levels of alpha-feto protein decline, the effectiveness of E2 increases [9, 51,59], becoming maximal during juvenile days [9,14]. The capaci ty of E2 to keep gonadotropin secretion in check remains fully operative unitl the very day of first proestrus [9].…”
Section: Steroid Negative Feedbackmentioning
confidence: 99%
“…On the basis of early findings (Donovan & van der Werff ten Bosch, 1959) and those obtained from steroid replacement studies after gonadectomy (Ojeda & Ramirez, 1973 ;Steele & Weisz, 1974), the concept grew that as maturity progressed there was a decrease in sensitivity of brain-pituitary mech¬ anisms to negative feedback, and that this might in some way account for the onset of puberty. However, Odell & Swerdloff (1976) have found that testosterone treatment, initiated on the day of castration, lowers serum LH concentrations equally well in 10-and 21 -day-old as in 73-day-old males ; the dose of testosterone required to lower post-castration FSH values was smaller in the youngest animals, although similar doses were required for 21-and 75-day-old animals.…”
Section: Negative Feedbackmentioning
confidence: 99%